Speech Function on the Text Romeo and Juliet Drama - Artha, D J; ., Listiani (KnE Social Sciences, 2018)
This research deals with speech function on the text Romeo and Juliet Drama. The objective of this study is to find out the types of speech function and the most dominant types of speech function on the test Romeo and Juliet Drama. Descriptive qualitative method was carried out to analyze the data. Source of data of this research would be taken from the text Romeo and Juliet Drama. Of the selected act, act 1 scene I to III, act 3 scenes I to V, and act 5 scene I to II. In collecting the data, some references related to speech function found out in the library. In analyzing the data, first each sentence in each act from the text Romeo and Juliet is underlined, second to identify the types of speech function which are mostly dominant, and the last to find the dominant type of speech function. The text of Romeo and Juliet drama were analyzed on the occurrences of speech function based on the types of speech function on the text Romeo and Juliet drama. There were 265 items, namely statements 154 items (58%), commands 41 items (15,5%), questions 40 items (15%), and offers 30 items (11,5%). And the dominant speech function is statements 154 items (58%). Keywords: Speech function, drama, statement, command, question, offer